Cis P-tau is induced in clinical and preclinical brain injury and contributes to post-injury sequelae - Onder Albayram (Nature Portfolio, 2017)
Induction of the cis form of phosphorylated tau (cis P-tau) has previously been shown to occur in animal models of traumatic brain injury (TBI), and blocking this form of tau using antibody was beneficial in a rodent model of severe TBI. Here the authors show that cis P-tau induction is a feature of several different forms of TBI in humans, and that administration of cis P-tau targeting antibody to rodents reduces or delays pathological features of TBI.